The Relationship between Parenting and Motor Development of Pre-School Children at Mawar Kindergarten, Bubeya Village, Bone Bolango Regency - Fidya Rachmawati Konili; Andi Akifa Sudirman; Dewi Modjo (Universitas Muhammadiyah Palu, 2026)
Children at preschool age have a lot of potential to develop. Children's motor development can be in the form of fine motor development and gross motor development. The normal development pattern in every child is not always the same and can be influenced by several factors, one of which is parental parenting. This study aims to determine the relationship between parental parenting and motor development of pre-school children in Mawar Kindergarten, Bubeya Village, Bone Bolango Regency. This study uses a cross-sectional study approach. The research sample was 37 respondents determined by total sampling technique. Data collection was done using observation sheets and questionnaires. The data was analyzed using a chi square statistical test. The results of the study were obtained that parents of preschool children mostly applied permissive parenting, namely as many as 16 parents or 43.2%, gross motor development was mostly in the suspect category, namely 21 children or 56.8% and fine motor development was mostly in the suspect category, namely 22 children or 59.5%. The results of the chi square test had a p value of 0.001 (p value < ? 0.05) which means that there is a meaningful relationship between parental parenting and fine motor development and gross motor development of preschool-age children. The conclusion of the study is that there is a relationship between parental parenting and fine motor development and gross motor development of preschool-age children at Mawar Kindergarten, Bubeya Village, Bone Bolango Regency. It is recommended to schools that are expected to help in improving parental knowledge, attitudes, behaviors and provide knowledge about the importance of parenting with fine motor development in preschool-age children.